Strategi Guru dalam Menerapkan Model Pembelajaran Flipped Classroom Berbantu E-Learning pada Mata Pelajaran PAI di MAN 2 Tuban - Affida, Laili Nur; Zainiyati, Husniyatus Salamah (QUALITY, 2022)
The application of conventional learning models tends to make students passive when participating in teaching and learning activities in class. Therefore, teachers are required to be creative in designing fun and meaningful learning for students. One of the efforts that teachers can make to make the classroom atmosphere effective and active is by implementing the flipped classroom learning model. This study aims to determine the teacher's strategies and steps in implementing the fipped classroom learning model in the Islamic Cultural History subject at MAN 2 Tuban. The research method applied in this study is a descriptive qualitative research method to describe the strategies and steps of the teacher in implementing the flipped classroom learning model.